Secrets at sea - Peck, Richard, 1934-; Murphy, Kelly, 1977- (New York : Dial Books for Young Readers, 2011)
In 1887, the social-climbing Cranstons voyage from New York to London, where they hope to find a husband for their awkward older daughter, secretly accompanied by Helena and her mouse siblings, for whom the journey is both terrifying and wondrous as they meet an array of titled humans despite their best efforts at remaining hidden.
Keywords: Adventure and adventurers -- Fiction; Mice -- Fiction; Ocean travel -- Fiction; Human-animal relationships -- Fiction; Social classes -- Fiction; Brothers and sisters -- Fiction; Atlantic Ocean -- History -- 19th century -- Fiction